Knowledge Management and Organizational Performance: The Mediating Role of Dynamic Capabilities - Muzakar Isa; Fauziah Ar Rahmah (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2023)
This research examines the effect of knowledge management on organizational performance, with dynamic capability as a mediating variable. A quantitative research approach was applied. A survey was conducted using purposive random sampling. Data were collected manually by using a questionnaire. SmartPLS3 was used to analyze the data. The results showed that dynamic capability has been verified to mediate the relationship between knowledge management and performance. Greater knowledge management leads to higher performance, especially if the mediated dynamic capability is also greater. The managerial implications were that knowledge management and dynamic capability have prominent roles in organizational performance. Knowledge management and dynamic capability allow managers to optimize their creativity and innovation to develop ideas, which helps maximize the growth of organizational performance. The results supported the knowledge-based view (KBV). KBV serves as the foundation for comprehension of knowledge-based organizational theory. Knowledge significantly affects sustainable performance.